2020
DOI: 10.3390/ijms21030765
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calmodulin in Tumor Cell Migration, Invasiveness, and Metastasis

Abstract: Calmodulin (CaM) is the principal Ca2+ sensor protein in all eukaryotic cells, that upon binding to target proteins transduces signals encoded by global or subcellular-specific changes of Ca2+ concentration within the cell. The Ca2+/CaM complex as well as Ca2+-free CaM modulate the activity of a vast number of enzymes, channels, signaling, adaptor and structural proteins, and hence the functionality of implicated signaling pathways, which control multiple cellular functions. A basic and important cellular func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 339 publications
1
60
0
1
Order By: Relevance
“…More importantly, the promotion of cell migration by Tpl2 was dependent on both pathways. PLC-mediated Ca 2+ influx has been demonstrated to promote the disassembly of focal adhesions at the rear of migrating cells and assembly of focal adhesions at the leading edge, an essential event in migrating cells [27,108]. In support of this study, there is mounting evidence of the ability of the downstream effectors of PLCγ, PKC and Ca 2+ to support cell migration, by regulating cell adhesion turnover and acto-myosin contractility [46].…”
Section: Plcs In Cell Migration Invasiveness and Metastasismentioning
confidence: 52%
“…More importantly, the promotion of cell migration by Tpl2 was dependent on both pathways. PLC-mediated Ca 2+ influx has been demonstrated to promote the disassembly of focal adhesions at the rear of migrating cells and assembly of focal adhesions at the leading edge, an essential event in migrating cells [27,108]. In support of this study, there is mounting evidence of the ability of the downstream effectors of PLCγ, PKC and Ca 2+ to support cell migration, by regulating cell adhesion turnover and acto-myosin contractility [46].…”
Section: Plcs In Cell Migration Invasiveness and Metastasismentioning
confidence: 52%
“…In human body, CaM transmits information to many interaction partners by sensing local changes in Ca2 + concentration. Ca2+/CaM complex can modulate the activities of enzymes, channels, signals, adaptor and structural proteins, thereby regulating the functions of related signalling pathways that control various cell functions 21‐23 . It is reported that CaM can regulate cell growth and its function may change in malignant tumours 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Calmodulin (CaM) is a multifunctional Ca 2+ binding protein. Its role in metastatic traits was recently reviewed by Villalobo, and Martin, providing valuable insight into the roles of calmodulin in metastasis, from invasiveness to tumour cell migration [ 136 ]. It was shown that calcium/calmodulin-dependent protein kinase II (CaMKII) triggered gastric cancer cell metastasis by activating nuclear factor-κB (NF-κB) signalling involving AKT, which ultimately enhanced MMP-9production in BGC-803 cells (an in vitro model of human gastric cancer) [ 137 ]; this is a metastatic prompting protein present in various cancer subtypes.…”
Section: Proteins Involved In Ca 2+ Signalling mentioning
confidence: 99%